Array comparative genomic hybridization identifies high level of PI3K/Akt/mTOR pathway alterations in anal cancer recurrences - Wulfran Cacheux; Petros Tsantoulis; Adrien Briaux; Sophie Vacher; Pascale Mariani; Marion Richard‐Molard; Bruno Buecher; Sophie Richon; Emmanuelle Jeannot; Julien Lazartigues; Etienne Rouleau; Odette Mariani; et al. (Cancer Medicine, 2018)
Abstract Genomic alterations of anal squamous cell carcinoma (ASCC) remain poorly understood due to the rarity of this tumor. Array comparative genomic hybridization and targeted gene sequencing were performed in 49 cases of ASCC. The most frequently altered regions (with a frequency greater than 25%) were 10 deleted regions (2q35, 2q36.3, 3p21.2, 4p16.3, 4p31.21, 7q36.1, 8p23.3, 10q23.2, 11q22.3, and 13q14.11) and 8 gained regions (1p36.33, 1q21.1, 3q26.32, 5p15.33, 8q24.3, 9q34.3, 16p13.3, and 19p13.3). The most frequent minimal regions of deletion (55%) encompassed the 11q22.3 region containing ATM, while the most frequent minimal regions of gain (57%) encompassed the 3q26.32 region containing PIK3CA. Recurrent homozygous deletions were observed for 5 loci (ie, TGFR2 in 4 cases), and recurrent focal amplifications were observed for 8 loci (ie, DDR2 and CCND1 in 3 cases, respectively). Several of the focal amplified genes are targets for specific therapies. Integrated analysis showed that the PI3K/Akt/mTOR signaling pathway was the pathway most extensively affected, particularly in recurrences compared to treatment‐naive tumors (64% vs 30%; P = .017). In patients with ASCC recurrences, poor overall survival (OS) was significantly correlated with a large number of altered regions (P = .024). These findings provide insight into the somatic genomic alterations in ASCC and highlight the key role of the druggable PI3K/Akt/mTOR signaling pathway.